Grassland Communities in Dry Tropical Forests - Agarwal, S. C. (Indian Forester, 1961)
Grassland Communities occurring in Dry Tropical Forests are described and discussed. The three grassland types already discussed under Moist Tropical Forests also appear in Dry Tropical Forests, but here they develop luxuriantly and express their potential to the best extent due to lesser competetion from shrub growth. Inordinate biotic influence, however, may give a set back.